Contemporary Management and Prevention of Vaso-Occlusive Crises (VOCs) in Adults With Sickle Cell Disease. (February 2023) - Weaver, Salome Bwayo; Rungkitwattanakul, Dhakrit; Singh, Divita
Sickle cell disease (SCD) is a hematological disorder that primarily affects individuals of African descent from sub-Saharan Africa and along the mediterranean. The main complications leading to hospitalizations include vaso-occlusive crises (VOCs) and acute chest syndrome (ACS). Therefore, the main objective of this paper was to identify and evaluate evidence-based management and prevention of VOCs in patients with SCD. A literature search of PubMed, Medline Cochrane and Google Scholar database (January 1985 to April 2020) was performed using the following search terms "vaso-occlusive crises", "sickle cell disease", "hydroxyurea", "L-glutamine", "voxelotor", "crizanlizumab", "treatment" and "prevention" as well as a combination of these terms. All English-language interventional studies assessing the efficacy and safety of VOC outcomes were evaluated. Literature was excluded if published in a language other than English or if it was a review article. A total of 69 articles were identified and there were 7 articles that met the search criteria. Majority of the studies focused on mean and median annual rates of VOCs as primary outcomes while median time to first sickle cell crises, median rates of hospitalizations etc were evaluated as secondary outcomes. After reviewing the literature, many patients with VOCs will still benefit from hydroxyurea therapy since long term efficacy data and cost is still a concern for the newer agents including L-glutamine, voxelotor and crizanlizumab. Other factors such as cost or compliance may also be taken into consideration when making recommendations for therapy.